Further norm and numerical radii inequalities for operators involving a positive operator - Altwaijry, Najla (2025)
The article examines inequalities for norms and numerical radii of bounded linear operators on complex Hilbert spaces. It focuses on scenarios where three operators are involved, with one being positive, and investigates their sums or products. Some of our findings extend existing inequalities established in the literature.